Social support demands of families with children with cerebral palsy - Elizane Regina Santos Sandor; Sonia Silva Marcon; Noeli Marchioro Liston Andrade Ferreira; Giselle Dupas (Universidade Federal de Goias, 2014)
Cerebral Palsy (CP) has significant repercussions in the family. The goal of the present study is to investigate the demands for social support of families with children with CP, as well as the repercussions of such demands in the child's care. It is a descriptive-exploratory qualitative study, conducted with seven families whose children are attended to in a children's outpatient clinic. The following categories emerged from the interview analysis: "demands for family support;" disbelief in the support network;" "impaired interaction with professionals" and "carrying on despite everything." The demand for social support is evident, and it is essential that public policies and institutional and professional ties be implemented so that the family of a child with CP can receive integral and humanized assistance. doi: 10.5216/ree.v16i2.21112.